Interconnections between Emotion Recognition, Self-Processes and Psychological Well-Being in Adolescents - Meghan L. Maynard; Shanel Quenneville; Kristina Hinves; Victoria Talwar; Sandra L. Bosacki (MDPI AG, 2022)
Background: Adolescence is a critical developmental period for mentalization and emotion regulation skills. Studies show that during this time, adolescents may experience greater vulnerability to challenges of mental and emotional well-being. Studies also show that self-skills, such as mentalization, self-compassion, and self-control are independently associated with feelings of global self-worth or psychological well-being. To date, no known studies have explored interconnected relations among these self-skills, despite significant overlaps in the social-biological development of these skills. Aims: To investigate interconnected relations among psychological well-being, mentalization, self-compassion and self-control. Gender differences in these relations are explored. Method: As part of a larger, longitudinal study of adolescent well-being, this cross-sectional study drew on a variety of self-report measures, investigating relations among adolescents' self-reports of psychological well-being, emotion recognition, self-control, and self-compassion. Participants consisted of 88 girls and 57 boys, mean age 13.38. Results: Main results showed associations among emotion recognition, self-control and self-compassion and feelings of global self-worth. Specifically, results showed that understanding negative emotions in others relates to lower levels of self-compassion and feelings of self-worth. Further, adolescents who report low levels of self-control reported uncompassionate self-responding and lower levels of self-worth. Gender differences and implications for further research and adolescent social-emotional interventions are discussed.